Grandmothering, menopause, and the evolution of human life histories - Hawkes, K. (The National Academy of Sciences, 1998)
Long postmenopausal lifespans distinguish humans from all other primates. This pattern may have evolved with mother–child food sharing, a practice that allowed aging females to enhance their daughters’ fertility, thereby increasing selection against senescence. Combined with Charnov’s dimensionless assembly rules for mammalian life histories, this hypothesis also accounts for our late maturity, small size at weaning, and high fertility. It has implications for past human habitat choice and social organization and for ideas about the importance of extended learning and paternal provisioning in human evolution.